Programmed Cell Death Ligand (PD-L)-1 Contributes to the Regulation of CD4+ T Effector and Regulatory T Cells in Cutaneous Leishmaniasis - Freitas e Silva, Rafael de; Gálvez, Rosa Isela; Pereira, Valéria Rego Alves; de Brito, Maria Edileuza Felinto; Choy, Siew Ling; Lotter, Hannelore; Bosurgi, Lidia; Jacobs, Thomas (Frontiers in Immunology, 2020)
Cutaneous Leishmaniasis (CL) affects up to one million people every year and treatments are costly and toxic. The regulation of the host immune response is complex and the knowledge of how CD4+ T cells are activated and maintained during Leishmania infection is still limited. Current therapies aim to target programmed cell death (PD)-1 and programmed cell death ligand (PD-L)-1 in order to boost T cell activity. However, the role of the PD-1/PD-L1 axis during Leishmania infection is still unclear. In this study, we found that patients with active and post-treatment CL displayed different subsets of CD4+ PD-1+ T cells. Accordingly, L. major-infected mice upregulated PD-1 on activated CD4+ T effector cells and PD-L1 on resident macrophages and infiltrating monocytes at the site of infection. L. major-infected Pdl1-/- mice expressed lower levels of MHCII and higher levels of CD206 on macrophages and monocytes and, more importantly, the lack of PD-L1 contributed to a reduced frequency of CD4+Ly6Chi T effector cells and an increase of CD4+Foxp3+ regulatory T cells at the site of infection and in draining lymph nodes. Additionally, the lack of PD-L1 was associated with lower production of IL-27 by infiltrating monocytes and lower levels of the Th1 cytokines IFN- and TNF- produced by CD4+ T effector cells. Pdl1-/- mice initially exhibited larger lesions despite having a similar parasite load. Our results describe for the first time how the interruption of the PD-1/PD-L1 axis influences the immune response against cutaneous leishmaniasis and suggests that this axis regulates the balance between CD4+Ly6Chi T effector cells and CD4+Foxp3+ regulatory T cells.